2015
DOI: 10.1021/acs.macromol.5b01441
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic and Mechanistic Studies of the Polymerization of Isobutylene Catalyzed by EtAlCl2/Bis(2-chloroethyl) Ether Complex in Hexanes

Abstract: The kinetics and mechanism of the polymerization of isobutylene (IB) initiated by tert-butyl chloride and catalyzed by ethylaluminum dichloride (EADC)•bis(2-chloroethyl) ether (CEE) complex was studied in hexanes at 0°C. The polymerization is first order in [IB] and in dry hexanes the slopes of the first order plots are independent of the [CEE]/ [EADC] ratio in the range 1−1.5. From the slopes the steady state concentration of propagating cations [M n + ] = 1.8 × 10 −11 M was calculated, which suggests an equ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
47
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(49 citation statements)
references
References 32 publications
2
47
0
Order By: Relevance
“…Some major drawbacks for the new HR PIB process systems include low process temperatures and/or use of polar chlorinated solvents that present serious limitations for industrial application . Recently, we reported an ethylaluminum dichloride (EADC) · bis(2‐chloroethyl) ether (CEE) complex as a fully hydrocarbon soluble catalyst that in conjunction with tert ‐butyl chloride ( t ‐BuCl) initiator in hexanes at 0–20 °C gave HR PIB with quantitative yields and up to 92% exo‐olefin end‐functionality . In these studies, polymerizations were carried out under high purity conditions, which may be difficult to maintain in industry.…”
Section: Introductionsupporting
confidence: 90%
See 3 more Smart Citations
“…Some major drawbacks for the new HR PIB process systems include low process temperatures and/or use of polar chlorinated solvents that present serious limitations for industrial application . Recently, we reported an ethylaluminum dichloride (EADC) · bis(2‐chloroethyl) ether (CEE) complex as a fully hydrocarbon soluble catalyst that in conjunction with tert ‐butyl chloride ( t ‐BuCl) initiator in hexanes at 0–20 °C gave HR PIB with quantitative yields and up to 92% exo‐olefin end‐functionality . In these studies, polymerizations were carried out under high purity conditions, which may be difficult to maintain in industry.…”
Section: Introductionsupporting
confidence: 90%
“…As per our previous report, the polymerization obtained in wet hexanes at [CEE]/[EADC] = 1.5 is identical with that determined for dry hexanes . Here, we demonstrated that water is not a necessary element in the case of polymerization without impurities under the specific conditions described in the experimental part.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…More recently, some groups employed the soluble complex of ethylaluminum dichloride (EADC) and bis(2chloroethyl)ether (CEE) as catalyst, tert-butyl chloride (t-BuCl) as initiator, to overcome the limitations in the previous methods. [30][31][32][33][34] The HRPIBs with high content of exo-olen end groups (>80%), adjustable molecular weight and almost 100% conversion within 20 minutes could be attained in hexanes. However, the products exhibit broad molecular weight distribution (PDI) due to the poor performances of batch reactor in transfer and dynamic control.…”
Section: Introductionmentioning
confidence: 99%